Message Queuing Telemetry Transport dalam Internet of Things menggunakan ESP-32 - Moh Noor Al-Azam; Darian Rizaludin; Yulius Satmoko Raharjo; Aryo Nugroho (STMIK Budi Darma, 2019)
Message Queuing Telemetry Transport (MQTT) is a connectivity protocol between machines or now better known as the Internet of Things (IoT). This protocol recognizes two basic functions of M2M communication, namely publish and subscribe (pub/sub). The MQTT protocol is designed as a very simple and very lightweight message delivery protocol, designed for devices that are limited and with low bandwidth capacity, high latency or on an unreliable network. The design principles are to minimize bandwidth requirements and device resource requirements, and keep trying to ensure reliability and guaranteed delivery rates. In this paper, VerneMQ performance reliability is tested - one of the MQTT brokers, with several stressing levels using ESP-32 as a publisher and notebook with the python application as a subscriber.